A Unified Feature Model for Scrum Artifacts from a Literature and Practice Perspective - Garcia, Luciano A.; OliveiraJr, Edson; Leal, Gislaine Camila L.; Morandini, Marcelo (Anais da Escola Regional de Engenharia de Software (ERES), 2020)
Scrum has become one of the most popular Agile methods. Among its main elements are its artifacts. These artifacts are related to the requirements required for the software and how they will be worked on during a Scrum interaction called Sprint. Given the importance of artifacts in the Scrum structure, evidence of the adaptations of these artifacts was collected with the aid of a systematic mapping study and a survey literature with practitioners of the method. Later, we systematized the evidence of adaptations found and built models of features in order to register them and enable users of the methods to have a broader understanding of the features that Scrum artifacts can assume.